0551 Movement Parasomnias in a Community Sample: Associations with Sleep Health and Mental Health. (25th May 2022) - Thesz, Isadora; Hale, Lauren; Branas, Charles; Killgore, William; Wills, Chloe; Grandner, Michael
Abstract: Introduction: Movement-related parasomnia symptoms are associated with several sleep disorders and are associated with adverse health, mental health, and social outcomes. Current literature lacks data regarding parasomnia prevalence in the general population. This study examined prevalence of these symptoms and correlates in a community-based sample. Methods: Data were from the Sleep and Healthy Activity, Diet, Environment and Socialization (SHADES) study, consisting of N=1, 007 working-age adults. Parasomnia symptoms were assessed with, "I have been told that I walk, talk, eat or act strange or violent while sleeping." Responses were categorized as Never (1/year or less), Sometimes (<1/week), or Often (>=1/week). Sleep health variables included sleep duration, categorized as very short (<=4h), short (5-6h), normal (7-8h, reference group) or long (>=9h), Insomnia Severity Index, Epworth Sleepiness Scale, Fatigue Severity Scale, Brief Index of Sleep Control, frequency of loud snoring, and frequency of sleep medication use. Mental health variables included PHQ9 depression score, GAD7 anxiety score, Perceived Stress Scale, and self-reported survival of severe physical/emotional trauma (None, Possible, Definite). Covariates included age, sex, race/ethnicity, education, income, employment, and body mass index. Results: Parasomnia symptoms were reported sometimes by 24% and often by 7% of the sample. The following sleep-related variables were associated with more movement-related symptoms sometimes: very short sleep (RRR=2.26), higher ISI (RRR=1.08), ESS (RRR=1.09), and FSS (RRR=1.05), and frequent snoring (RRR=2.84). The following were associated with more symptoms often: very short sleep (RRR-4.40), higher ISI (RRR=1.18), ESS (RRR=1.18), FSS (RRR=1.07), frequent snoring (RRR=7.38) and medication use (RRR=5.99), and less sleep control (RRR=0.43). Regarding mental health, more symptoms sometimes or often was associated with higher depression (RRR=1.11 and 1.16, respectively), anxiety (RRR=1.12 and 1.17, respectively), and stress (RRR=1.06 and 1.10, respectively) scores. Trauma survivors were more likely to report symptoms often (RRR=4.78). Conclusion: Movement-related parasomnia symptoms are fairly prevalent and may impact nearly one third of community-dwelling working-age adults. Those exhibiting symptoms are more likely to experience shorter sleep duration, poor sleep quality, daytime dysfunction, and worse mental health. Screening efforts for subclinical symptoms should be increased, and further work should explore pathways linking these symptoms to health and functional outcomes. Support (If Any):